Math Teacher and e-Learning Courses. Report on the Project “Modern Mathematics Teacher” - Kandzia, Joanna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The article is a report on the project conducted by the author, co-financed by the National Center for Research and Development from European funds POWR.03.01.00-IP.08-00-MOC/18 entitled: A modern mathematics teacher. It was dedicated to teachers of mathematics from all over the country, teaching in primary and secondary schools, and future mathematics teachers – gaining qualifications to teach mathematics. The project aimed to improve the quality and efficiency of mathematics teachers’ work through active participation in innovative e-learning courses – offered on the navoica.pl platform, concerning new teaching methods based on information technologies. A short description of the four proposed e-learning courses is presented, as well as an analysis of the choices made by the participants depending on the subject.
Keywords: algebra; competition tasks; e-learning; mathematical education; mathematical modeling; mathematics teacher; multimedia